Evaluación del biodiésel producido a partir de aserrín de café bajo un proceso de transesterificación a nivel laboratorio como fuente de energía alternativa (2020)
The biodiesel produced from coffee sawdust oil was evaluated giving rise to a second generation production where the management of a daily waste was sought, identifying variables and influencing factors both in the process of oil extraction and transesterification. The extraction operation was carried out by means of a soxhlet extractor using hexane and Isopropanol as solvents, based on the incident conditions when carrying out the extraction. The extracted oil was characterized by determining the acid number, iodine index, saponification, the percentage of oil extracted, density and viscosity in the laboratory.